PSYCHOLOGICAL PERSONALITY TRAITS OF SEXUAL OFFENDERS - Todoroska Gjurchevska, Slobodanka; Ibish, Ebru (International Scientific Journal Vision, 2022)
Criminality is an extremely heterogeneous social phenomenon that includes various kinds of deviant behavior. It also includes sexual criminality (crimes against sexual freedom and moral), which has a highly negative impact on society and endangers the most intimate parts of a person’s life. The aim of this survey is to outline a structure of psychological features of sexual offenders, to determine the degree of their development and the way in which they are connected. The results that have been achieved during this survey will successfully be implemented into the practical work of penal institutions in the Republic of Macedonia in order to ensure successful resocialisation and reintegration of sexual offenders in the society. Our experience and knowledge are compatible with world-wide trends saying that sexual offenders are mentally healthy people and that they cannot be included in any diagnostic category. The main results of this survey can be summed up into several points: in general, sexual offenders are male, aged between 26 and 33, with minimal education and without profession or employment. Usually, they do not behave in pathological manner and they are mentally healthy people. It is believed that resocialisation as well as complex treatment will be necessary for people convicted of sexual offences; not only will it represent prevention from committing new crimes, it will also be a breeding ground for their active participation in life out of the penal institutions.